1989
DOI: 10.1016/s0022-5347(17)41212-2
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Acid-Fast Bacilli Following Intravesical Bacillus Calmette-Guerin

Abstract: Intravesical bacillus Calmette-Guerin immunotherapy has great efficacy in the treatment of superficial transitional cell carcinoma of the bladder. We report a case of persistent acid-fast bacilli contained within granulomas of the bladder, prostate and epididymides 1 year after treatment with intravesical bacillus Calmette-Guerin. Although commonly encountered immediately after therapy, there are no reported cases of persistent acid-fast bacilli following intravesical administration of bacillus Calmette-Guerin. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In 3 of these patients, acid-fast bacilli were demonstrated within the prostate. Linn et al reported the case of a patient who had undergone radical cysto-prostatectomy 1 year after BCG treatment failure [4], In this patient, acid-fast bacilli were found within the granulomas of the bladder, prostate and epididymis.…”
Section: Loco-regional Disseminationmentioning
confidence: 89%
“…In 3 of these patients, acid-fast bacilli were demonstrated within the prostate. Linn et al reported the case of a patient who had undergone radical cysto-prostatectomy 1 year after BCG treatment failure [4], In this patient, acid-fast bacilli were found within the granulomas of the bladder, prostate and epididymis.…”
Section: Loco-regional Disseminationmentioning
confidence: 89%
“…Introduction mentation of the prostate) within a year before the diagnosis of GP. Granulomatous inflammation of the prostate has been reported in some patients after receiving bacillus 4 No history of BCG instillation in the bladder, Wegener's granulomatosis, systemic vasculitis, or infec-Calmette-Guérin (BCG) therapy for bladder cancer [1,2], after transurethral resection of the prostate [3]…”
mentioning
confidence: 99%
“…Linn et al . [3] described granulomas of the bladder, prostate and epididymidis 1 year after BCG treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Persistence of BCG in urine or bladder biopsies more than 3 months after the last instillation is rare. There are, to our knowledge, only four published case reports with six patients who had a late BCG infection with inflammatory changes in the urinary bladder [3–6]. At cystoscopy, the bladder mucosa was described as either inflamed or showed scattered granulomas.…”
Section: Introductionmentioning
confidence: 98%